Understanding Root Growth Dynamics in Plants Under High Temperature Stress - Lale, Aneesh (2024)
Rapid industrialisation in the last few centuries has led to a significant increase in land temperatures due to the increase in atmospheric concentrations of greenhouse gases. This warming effect increases the frequency of extreme temperature events leading to a higher probability of heat waves, which threaten agricultural output and food security. It is important to study the effects of heat stress on crop productivity, and for that we need a strong understanding of how plants react to elevated temperatures. Currently, we have decades worth of literature on the effects of heat on photosynthesis and reproduction in plants, yet a major component of heat response is still relatively unknown. The root system, aptly known as the ‘hidden half’ of the plant has been shown to sense and react to elevated temperatures but the exact molecular mechanisms of stress response in the root present themselves as a gap in our current understanding. Recent literature suggests that the root system may be more susceptible to higher temperatures than the shoot, and this makes it crucial to understand the effects of high temperature on roots. In this literature review, we discuss the predictions and simulations that point towards a warmer future and what this means for our agricultural system. We explore temperature sensing in roots, an important process, yet the mechanisms of which are still debated. Biochemical and molecular mechanisms of heat response are discussed with a special focus on how the root system has been shown to react to heat stress. Natural variation and genetic improvements in plant heat tolerance, both of which are important tools towards breeding more heat resilient crops, are also considered. This thesis aims to help us better understand the heat stress responses in roots, so that it may aid in breeding more climate proof crops.